Comparison of Five Growth Charts for Identifying Small-Sized Fetuses and Their Predictive Value for Adverse Neonatal Outcomes - Bayrak, Ayse Cigdem; Fadiloglu, Erdem; Gungor, Betul; Caner Çabukoğlu, Fatma; Gasimova, Shahla; Kayikci, Umutcan; Deren, Ozgur (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
The main goal of fetal growth monitoring is to identify fetuses at increased risk of morbidity and mortality. This study compares 5 commonly used growth charts (Hadlock, FMF, NICHD, INTERGROWTH-21st, WHO) to assess their ability to identify pregnancies below the 10th percentile and predict adverse neonatal outcomes.We retrospectively analyzed 572 singleton pregnancies with an estimated fetal weight (EFW) <10th percentile according to Hadlock, excluding multiple pregnancies or cases with maternal comorbidities. Maternal and neonatal data were collected, and EFW and birthweight percentiles were recalculated using the different growth charts. Statistical analyses assessed the association between these charts and adverse neonatal outcomes.The WHO chart classified the fewest pregnancies below the 10th percentile and showed significant differences in composite adverse outcomes between the groups (p < 0.05). Despite a lack of statistical significance, the WHO chart had better prediction for NICU admission compared to others. At the 3rd percentile cutoff, all charts showed similar results for NICU admission and adverse outcomes (p < 0.01). For severe adverse outcomes, only the WHO and FMF charts showed significant differences (p = 0.043, p = 0.029).The WHO chart showed superior performance at the 10th percentile cutoff, while all charts were comparable at the 3rd percentile. Notably, the WHO and FMF charts significantly differentiated between patients with severe composite adverse outcomes at the 3rd percentile to improve the accuracy of diagnosing and predicting neonatal outcomes in small-sized fetuses.
Keywords: birth weight percentile; ultrasonography; fetal biometry; estimated fetal weight